2017
DOI: 10.1093/bioinformatics/btx681
|View full text |Cite
|
Sign up to set email alerts
|

MetaCherchant: analyzing genomic context of antibiotic resistance genes in gut microbiota

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…We also positioned MetaCherchant software [18] as a valuable post-processing tool for our bioinformatics pipeline, allowing to obtain a reconstruction of the genomic context around detected ARG. While our original intention was to benchmark MetaCherchant with our pipelines, it could not directly compete in terms of ARG detection precision given the high similarity between ARG sequences in our ARG RDB.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also positioned MetaCherchant software [18] as a valuable post-processing tool for our bioinformatics pipeline, allowing to obtain a reconstruction of the genomic context around detected ARG. While our original intention was to benchmark MetaCherchant with our pipelines, it could not directly compete in terms of ARG detection precision given the high similarity between ARG sequences in our ARG RDB.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In addition to offering pathogen and ARG detection, our bioinformatics pipeline TBwDM can be complemented for understanding genomic context in the neighborhood of detected ARG. To illustrate this, we ran MetaCherchant [18], a graph-based algorithm for extracting ARG and their genomic context (sequence environment) from metagenomic data, on the simulated polymicrobial infections. Table 4 shows MetaCherchant performance at the sample level (i.e.…”
Section: Additional Insight On Detected Argmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient graph algorithms provide novel tools for investigating graph neighborhoods. Recent work has shown that incorporating the structure of the assembly graph into the analysis of metagenome data can provide a more complete picture of gene content (21,22). While this has provided evidence that it is useful to analyze sequence that has small graph distance from a query (is in a "neighborhood"), this approach has not been widely adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most assembly graphs undergo substantial heuristic error pruning and may not contain relevant content (11,12). Graph queries have shown promise for recovering sequence from regions that do not assemble well but are graph-proximal to the query (21,22). However, many graph query algorithms are NP-hard and hence computationally intractable in the general case; compounding the computational challenge, metagenome assembly graphs are frequently large, with millions of nodes, and require 10s to 100s of gigabytes of RAM for storage.…”
mentioning
confidence: 99%